Shot in America : television, the state, and the rise of Chicano cinema - Noriega, Chon A., 1961- (University of Minnesota Press, 2000)
Noriega offers a compelling and detailed description of an enormous body of work by Chicano media makers against the backdrop of Chicano social movements, politics, and activism over a forty-year period--an extraordinary exposition of the civil rights movement, media reform activities, and public affairs programming that constitutes the prehistory of independent and minority cinemas. 2000 Choice Outstanding Academic Title.
Keywords: Mexican Americans in motion pictures.; Mexican Americans on television.; Mexican Americans in the motion picture industry.; Américains d'origine mexicaine au cinéma.; Américains d'origine mexicaine à la télévision.; Américains d'origine mexicaine dans l'industrie cinématographique.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Mexican Americans in motion pictures; Mexican Americans in the motion picture industry; Mexican Americans on television; Filmwirtschaft; Fernsehen; Film; USA; Chicanos.